Water and Food restriction decreases immunoreactivity of oestrogen receptor alpha and antioxidant activity in testes of sexually mature Coturnix coturnix japonica. Issue 6 (1st June 2020) - Baghel, Kalpana; Niranjan, Mukesh K.; Srivastava, Rashmi
Abstract: Food and water are closely associated with reproductive willingness in vertebrates. These are important for animals and their non‐availability act as stressors which decrease sex steroid secretion suppressing reproductive behaviour. Oestrogen plays a crucial role in reproduction via its receptors alpha (ERα) and beta (ERβ). This study tested the hypothesis that ERα in testes of male Japanese quail is regulated during water and food deprivations. The present study reveals that both water and food deprivations cause oxidative stress and subsequently decrease catalase and superoxide dismutase activity, while these increase malondialdehyde and hydrogen peroxide. Both deprivations reduce plasma oestradiol whereas elevate corticosterone level. The immunofluorescent localization of ERα in the testes occurs predominantly in the seminiferous tubules of control while reduces after both food and water deprivations. All types of spermatogenic cells were seen in control testis, while after water and food deprivations size of seminiferous tubules and spermatogenic cells population decreased. Scanning electron microscopic study exhibited fully mature sperms in clusters with head and elongated flagellum, whereas after water deprivation maximum sperms were distorted, scattered with highly reduced head. On food deprivation, only few sperms were seen with head and tail. Thus, taking into account the localization of ERα in testis, it is obvious that oestrogens produced locally are involved in regulation of spermatogenesis and spermiogenesis during stress.